A microfluidic system, utilising image processing methods, for the detection of blood coagulation and erythrocyte aggregation - Louka, Marinos; Passos, Andreas; Inglezakis, Antonis; Loizou, Constantinos; Kaliviotis, Efstathios (My University, 2022)
Hemostasis is a defence mechanism that prevents blood losses in cases of vessel injuries, and other related disorders. In many cases, patients need to frequently monitor their blood coagulation tendency in order to regulate their medication. In addition, red blood cell aggregation (RBCA) is related to blood inflammation, and it appears elevated in many pathological conditions. Blood coagulation and RBCA can be studied by analysing the dynamic changes of light transmittance though a clotting/aggregating sample, and indeed various works in the literature exploit this approach. In this work, blood coagulation and RBCA are examined by utilising single drops of blood in an inexpensive camera-based microfluidic system, designed for low computational and production cost. Results are compared with a microscopy-camera system, with both setups utilizing the same custom made microchannel. Three image processing algorithms are developed to analyze the averaged light intensity, and the local structural chracteristics of blood, through a binarization and region classification method, using logical operations. The results illustrate the repeatability of the technique and the donor-to-donor variation within the proposed approach. Based on the image processing analysis, the developed coagulation and aggregation indices show great potential of utilisation in an inexpensive and robust point of care device.
Keywords: Pathology; Costs; Red blood cells; Image processing; Point of care; Coagulation; Production; Biomedical optical imaging; Biomedical optical imaging; Aggregation; Cellular biophysics; Medical image processing